Annotated checklist and keys for cumaceans (Crustacea: Peracarida) from the Tropical Eastern Pacific, with six new species from the Southern Mexican Pacific - Jarquín-González, Jani; García-Madrigal, María Del Socorro (Zootaxa, 2013)
In the Tropical Eastern Pacific (TEP) 23 species of cumaceans are known, however none of these species has been previously registered in the southern Pacific coast of Mexico. The examination of 378 specimens resulted in six new species, belonging to two families and five genera, Coricuma zurai sp. nov., Cyclaspis boquillensis sp. nov., Cyclaspis hyalinus sp. nov., Cumella (Cumewingia) carmeinae sp. nov., Elassocumella krakeri sp. nov. and Nannastacus corallinus sp. nov. The genus Coricuma Watling & Breedy, 1988, increases its geographical range from Costa Rica to Mexico, and a second species is described. Recorded for the first time in the Eastern Pacific are the genera Elassocumella Watling, 1991 and Nannastacus Bate, 1865. An annotated checklist and illustrated key to all species of cumaceans recognised from the Tropical Eastern Pacific are included.